Annuity in Advance for Rental Properties: Profit and Risk Analysis for Owners of Student Rental Homes Near Campus - Sabrina, Amirah Nur; Nabila, Hella Rizwa (Research Collaboration Community (RCC), 2024)
Nowadays, the rental homes business in the area around the campus offers significant profits for its owners, this is due to the large number of students who migrate so they choose to live in rental homess, but on the other hand this can also cause various risks, including fluctuations. Maintenance costs and high occupancy rates. This can make rental homes owners' income unpredictable and make it difficult to create long-term financial goals. Using an upfront annuity model, where the owner receives rental payments at the start of the period, is one way to lower this risk. rental homes owners can guarantee more consistent cash flow and make more accurate income predictions by applying this concept. The aim of this research is to examine how the application of the advance annuity model affects the income and risks of rental homes owners. This study will assess how advance annuities contribute to income stability and reduce the uncertainty that often occurs in rental homes operations by using comprehensive financial techniques. Apart from that, this analysis will also consider various external factors that can influence occupancy levels, such as campus policies and economic conditions. It is hoped that the findings from this research will provide useful insights for rental homes owners in maximizing profits while managing risks more effectively, so that they can adapt to ever-changing market dynamics. Therefore, this strategy can be a smart alternative for rental homes owners in optimizing their business performance around campus.